World-Class Universities and Institutional Autonomy in China - Blackburn Cohen, Chelsea (International Higher Education, 2019)
With the release of Scholars at Risk’s (SAR’s) Obstacles to Excellence: Academic Freedom and China’s Quest for World-Class Universities, institutional autonomy ascends to the fore. In China’s pursuit to transform its institutions into world-class universities, global rankings have offered metrics to purported advancement but too often lack consideration of academic freedom and institutional autonomy, permitting only a shrinking space for vital questions as China applies enormous effort to impose control while seeking the status of a world-class knowledge producer. This article is based on a Scholars at Risk’s report entitled Obstacles to Excellence: Academic Freedom and China’s Quest for World-Class Universities, available on SAR’s website at https://www.scholarsatrisk.org/.